Cooperation Between Home and School in the Finnish Core Curriculum 2014 - Miina Orell; Päivi Pihlaja (Universitetsforlaget i samarbeid med Nordisk forening for pedagogisk forskning, 2022)
This article examines, with the help of document analysis, how cooperation between home and school is presented in the Finnish National Core Curriculum for Basic Education 2014, which was implemented in autumn 2016. It was found that references to home-school cooperation comprise four themes: cooperation based on values, cooperation as a cultural meeting-point, cooperation to prepare for the future and support through cooperation. The precise guidance provided by the Curriculum on cooperation concentrates on actions performed at the individual level, which in turn steers the focus of cooperation towards the individual. Questions of communality are avoided, and the school as an institution is assumed to have endless resources to act. The multiple faces of cooperation between home and school and the effects and possibilities at the individual and community levels should be discussed more versatilely.